HUBUNGAN ASUPAN MAKANAN DENGAN PENAMBAHAN BERAT BADAN PADA REMAJA HAMIL USIA 15-19 TAHUN (Studi pada Kelurahan Rowosari Kota Semarang) - Awanis Farisa Setyarahma; Martha Irene Kartasurya; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2016)
Adolescent pregnancy need higher food intake than adult pregnant women, because they were still in the growth period. There were many cases (415) of adolescent pregnancy in Rowosari, Semarang in 2015. The purpose of this study was to analyze the association of energy, protein, fat, vitamin B1, vitamin B6, vitamin B12, and calcium adequacy levels and the weight gain among adolescent pregnanciesat Rowosari Village, Semarang. This study was an analytical study with a cross-sectional approach. The subjects were44 pregnant adolescent who were chosen purposively. Data were collected through interviews using structured questionnaires and 2 x 24 hours recalls. Qualitative data were also collected through indepth interviews. Data were analysed by Pearson and Spearman Rank correlation tests. The results showed that the adequacy level of energy was (79.5±8.55)%, protein (70.55±24.88)%, fat (52.3±22.54)%, vitamin B1 (90.9±22.99)%, vitamin B6 (65.9±24.30)%, vitamin B12 (56.8±79.21)% and calsium (59.1±49.83)%. There were correlation between energy adequacy levels (p = 0.000), protein adequacy level (p = 0.040), fat adequacy level (p = 0.032), vitamin B1 adequacy (p = 0.021), vitamin B6 adequacy (p = 0.034), calsiumadequacy levels (p = 0.016) and weight gain. There was no correlation between adequacy levels of vitamin B12 (p = 0.188) and the pregnancy weight gain. It was concluded that there were correlation between adequacy level of energy, protein, fat, vitamin B1, vitamin B6 and calcium with the pregnancy weight gain of adolescent pregnancy.